2015
DOI: 10.4274/jcrpe.1629
|View full text |Cite
|
Sign up to set email alerts
|

β-3AR W64R Polymorphism and 30-Minute Post-Challenge Plasma Glucose Levels in Obese Children

Abstract: Objective:In this study, we aimed to investigate the association of W64R polymorphism of the β3-adrenergic receptor gene (β-3AR) with childhood obesity and related pathologies.Methods:β-3AR gene W64R genotyping was carried out in 251 children aged 6-18 years. Of these subjects, 130 were obese (62 boys) and 121 were normal-weight (53 boys). In the obese group, fasting lipids, glucose and insulin levels were measured. Oral glucose tolerance test (OGTT) was performed in 75 of the obese patients.Results:The freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 39 publications
(50 reference statements)
1
11
0
Order By: Relevance
“…Obesity is a result of an imbalance between nutrient intake and energy expenditure (1). Due to the influence of technology and ever changing social structure, people now spend increasing amounts of their time in front of the television or computer.…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is a result of an imbalance between nutrient intake and energy expenditure (1). Due to the influence of technology and ever changing social structure, people now spend increasing amounts of their time in front of the television or computer.…”
Section: Introductionmentioning
confidence: 99%
“…There is still uncertainty regarding the genetic impact of the ADRB3 rs4994 polymorphism on the risk of childhood and adolescent overweight/obesity despite previous case-control studies [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Our systematic literature review and meta-analysis identified statistical significance under allele model, heterozygote model, and dominant model, which suggest that the C allele of this polymorphism could be a risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 239 individual publications initially identified, 16 unique studies [14][15][16][17][18][19][20][21][22][23][24][25][26][27]29,30] involving 5,147 overweight/obese cases and 7,350 non-obese controls were ultimately included for further synthetic analyses ( Figure 1). Totally, 69.9% of the included subjects came from East Asia.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies on this association have reported contradictory results. Other researchers have reported that ADRB3 polymorphism exhibits no effect on obesity, type 2 diabetes [21222324], or energy expenditure in obese post-menopausal women [25].…”
Section: Introductionmentioning
confidence: 99%